Foletti, Ivan; Kravcíková, Katarína; Palladino, Adrien y Rosenbergová, Sabina (eds.): “Migrating Art Historians on the Sacred Ways: Reconsidering Medieval French Art through the Pilgrim’s Body”. - Lucía Rodríguez Navarro (Los Libros de la Corte.es, 2023)
***